Identity Development and Maladaptive Personality Traits in Young Refugees and First- and Second-Generation Migrants - Zettl, Max; Akin, Zeynep; Back, Sarah; Taubner, Svenja; Goth, Kirstin; Zehetmair, Catharina; Nikendei, Christoph; Bertsch, Katja (Frontiers in Psychiatry, 2022)
Refugees are often exposed to a variety of stressors and traumatic events, posing a significant risk for the development of mental disorders. Young refugees may be particularly at risk because adverse life events affect identity formation, a developmental task that is typically expected in adolescence and emerging adulthood. Trauma and cultural changes may alter identity development, potentially leading to identity diffusion, a core concept of personality disorders. However, previous research on personality pathology among refugees is scarce. In this study, we examine identity development and maladaptive personality traits in young refugees and migrants. Refugees from 22 countries of origin were recruited in a German reception center (n = 120) and a group of adults with a migration background in first- or second generation was obtained via web-based recruitment (n = 281). Identity development was measured using the Assessment of Identity Development in Adolescence – Short Form. Maladaptive personality traits were assessed with the Personality Inventory for DSM-5-Brief Form. Group differences between refugees and migrants regarding identity development and trait expression were investigated using t-tests. The relationship between the two measures and their corresponding subscales was examined by means of correlation analyses. Refugees reported significantly higher levels of identity diffusion, negative affectivity, detachment, antagonism, and disinhibition compared to migrants. No significant differences were found for psychoticism. Correlation analyses revealed low to moderate positive associations between identity diffusion and maladaptive trait expression. Possible implications for early phase of resettlement, preventive psychiatric care and further research questions are discussed.